Underestimating Yourself: The EU and the Political Realities of the Eastern Neighbourhood. Issue 1 (June 2014) - Cornell, Svante E.
European leaders were taken by surprise by the Ukraine crisis and Russia's response to the Eastern Partnership. They should not have been: all questions raised by the Ukraine crisis first emerged with the 2008 war in Georgia. European leaders appear not to have grasped the fundamentally different forms of integration that the EU and Russia have proposed–-and especially the fact that voluntary European integration in the Eastern Partnership effectively negates Russia's need for weak, authoritarian states to form part of its restored empire. In responding to the crisis, EU leaders face a challenge from Russia that is asymmetric: Russia uses direct threats to the sovereignty of the EU's eastern neighbours, especially through unresolved conflicts, matters the EU is ill-equipped to handle. Finding ways to remedy this gap will be an important task for the EU in the immediate future.